Generalized synchronization of bidirectionally coupled chaotic systems - Khan, Mohammad Ali; Poria, Swarup (International Journal of Applied Mathematical Research, 2012)
This paper investigates the synchronization of Unified chaotic system and Rossler system via different methods. Several theorems for the synchronization of Unified chaotic system and Rossler system are deduced. Finally numerical simulation results are presented to show the feasibility and effectiveness of the approach. This synchronization method may be useful for sending secrete message and to understand synchronization of many biological systems, electronic circuits, chemical systems and potential applications to laser dynamics.